Specific Initiation Site for Simian Virus 40 Deoxyribonucleic Acid Replication - Thoren, Marilyn M. (1972)
Replicating simian virus 40 (SV40) deoxyribonucleic acid (DNA) molecules have been isolated under conditions in which the newly synthesized DNA is uniformly labeled with (3)H-thymidine. These newly synthesized strands are released from the replicative intermediate molecules by alkaline treatment, and it has been possible to isolate single-stranded SV40 DNA which varies in size from 157,000 daltons (from molecules that are 10% replicated) to 1,360,000 daltons (85% replicated). The rates of duplex formation of newly synthesized DNA have been used to relate their genetic complexity to the extent of DNA replication. As DNA replication proceeds, the time required to effect 50% renaturation of the newly synthesized DNA increases at a proportional rate. The data establish that DNA replication is not initiated at random, but rather that there is a single specific initiation site for DNA replication.